(untitled) (Experimental biology, 2015)
Quik climbing at 2750-3340 m cases the uprise of the heart freqrency and the decrease of heart rhythm variability. In had seen noted reduction neurohumoral influence value and the spectrum of the heart rhythm variability. There were marked predomination of tow frequent and very low frequent oscilation and diminuation of the high frequent ones in the spectrum. Desadoptive change of neurovegetative regulation have seen reised depending on the altitude.